Anak Nelayan Putus Sekolah: Studi Antropologi Budaya di Pesisir Selatan Jember - Adzkiyak , Adzkiyak (Education Journal : Journal Educational Research and Development, 2024)
This research examines the phenomenon of fishermen's children dropping out of school in the southern coastal area of Jember Regency, East Java, from the perspective of cultural anthropology. The study aims to uncover the social, economic and cultural factors that influence the high dropout rate among fisher children, as well as its impact on the dynamics of coastal communities. Using ethnographic methods, the study collected data through participant observation, in-depth interviews and document analysis over a period of one year. The main findings show that economic factors, such as poverty and the need to help the family economy, are the dominant causes of school dropout. However, cultural factors such as the community's perception of education, the tradition of fishing from an early age, and the lack of highly educated role models also play a significant role. This study also reveals the impact of dropping out of school on the sustainability of the fishing profession, social mobility, and community adaptation patterns to environmental and economic changes. The results of this study provide new insights into the complexity of education issues in coastal communities and highlight the importance of a holistic approach in formulating education policies that are sensitive to the local socio-cultural context. The implications of this study can serve as a foundation for the development of more effective intervention programmes to increase school participation and retention among fisher children, and promote sustainable development.